Enhancing Upper Limb Rehabilitation of Stroke Patients With Virtual Reality: A Mini Review - Bui, Julie; Luauté, Jacques; Farnè, Alessandro (Frontiers in Virtual Reality, 2021)
Upper limb motor impairment following stroke is a common condition that impacts significantly the independence and quality of life of stroke survivors. In recent years, scholars have massively turned to virtual reality (VR) to develop more effective rehabilitation approaches. VR systems are promising tools that can help patients engage in intensive, repetitive and task-oriented practice using new technologies to promote neuroplasticity and recovery. Multiple studies have found significant improvements in upper limb function for patients using VR in therapy, but the heterogeneity of methods and tools employed make the assessment of VR efficacy difficult. Here we aimed to assess the potential of VR as a therapy tool for upper limb motor impairment and to provide initial assessment of what is the added value of using VR to both patients and clinicians. Our mini-review focuses the work published since the Cochrane review (2017) and suggests that VR may be particularly effective when used in combination to conventional rehabilitation approaches. We also highlight key features integrated in VR systems that appear to influence rehabilitation and can help maximizing therapy outcomes, if exploited properly. We conclude that although promising results have already been gathered, more focused research is needed to determine the optimal conditions to implement VR in clinical settings in order to enhance therapy and to better define and leverage the true potential of VR. The rapid pace of technological development and increasing research interest toward VR-based therapy will help providing extensive knowledge and lead to rapid advancements in the near future.